Overhead cost allocation the case of an oil and gas company in Malaysia - Danila, Raudah; Amran, Noor Afza; Tahir, Agoos Munalis (Universiti Utara Malaysia, 2003)
Over the last forty years cost allocation has been the center of management accounting's literature. The criticisms made are mainly ranged from the allocation of fixed costs and overheads to responsibility division and to units of output. Many traditional overhead allocation systems result in misleading data that may have a negative impact on management decision making, budgeting, control and performance evaluation. This study aims is to look at the current practice of Malaysian oil and gas company in particular in allocating its overhead costs. In gathering the data on current practice and method used in cost allocation, series of interviews were conducted, site observation and review of related company documents. The research findings indicated that there is a difference in the cost allocation basis in the Head Office and the Regional Office. The cost allocation basis used at the Head Office is found to be solely dependent on the direct labor hour namely the time writing and percentage effort method. In contrast, the activities at the Regional Office are more diversified where most of the allocation was made based on the activity. The findings of this study is useful in providing better understanding on current practice in oil and gas industry particularly in allocating its overhead costs to each end products.